Chemical characterization and biological properties of oyster and shiitake mushrooms extracts and their liposomal formulations - Macit, Çağlar; Eyüpoğlu, Ozan Emre; Macit, Meltem; Zengin, Gökhan (My University, 2024)
In recent years, the production of liposomal formulations using mushroom extracts has gained increasing interest to increase the bioavailability of bioactive compounds in the nutraceutical field. Based on this information, we aimed to determine the antioxidant capacity (by DPPH, ABTS, CUPRAC and FRAP assays) and enzyme inhibition (against cholinesterase, amylase, glucosidase and tyrosinase) activities of alone and liposomal formulations of Pleurotus ostreatus (OYE) or Lentinus edodes (SHE) in different extracts solvents which were methanol (MeOH), aqua (Aq), methanol/aqua (MeOH/Aq). The extracts and formulations were chemically characterized using HPLC-DAD. The mean diameter of SL:SHE and SL:OYE (in MeOH/Aq) extended in range between 60 and 165 nm. The entrapment yields of SL:SHE and SL:OYE (in MeOH/Aq) were 63.8% ± 3.7% and 71.2% ± 2.8%, respectively. HPLC-DAD analysis revealed that ferulic and cinnamic acids were main components in the liposomal formulations. Liposomal formulations (in MeOH) showed higher antioxidant activity in the FRAP and CUPRAC assays. SL:SHE (in Aq) showed effective enzyme inhibition activity on acetylcholinesterase, tyrosinase, amylase and glucosidase enzymes. Based on our findings, the liposomal formulations can be a valuable strategy in preparing functional applications with shiitake and oyster mushrooms.
Keywords: Anti-Diabetic; Antioxidant; Functional Formulations; Mushrooms; Phenolics